Left Ventricular Reverse Remodeling and Function by Strain Analysis in Aortic Stenosis - Diana Filipa Pereira Azevedo (2020)
Introduction and Objectives: In severe aortic stenosis (AS), the impact of aortic valve replacement (AVR) on left ventricular (LV) systolic function assessed by strain measured by echocardiography or cardiac magnetic resonance (CMR) has been controversial. We aimed to investigate LV systolic myocardial function changes six months post-AVR using global longitudinal (GLS), circumferential (GCS) and radial (GRS) strain derived from CMR imaging. Methods: We included 39 severe AS patients (69.3±7.8 years; 61.5% male) with preserved LV ejection fraction (LVEF) who were recruited as part of the EPICHEART study and underwent successful AVR [aortic valvular area: 0.8 cm2 (IQR:0.2) pre- to 1.8 cm2 (IQR:0.5) post-AVR]. Structural and functional parameters were assessed at baseline and six months post-AVR, including LV GRS, GCS and GLS analysis by CMR, using cine short-axial and two-, three-, and four-chamber long-axial view. Comparison between baseline and postoperative LV remodeling was assessed using Student t-test and Wilcoxon test. Results: At six months post-AVR, LV mass, end-diastolic and end-systolic volumes, stroke volume, cardiac output, lateral E/e', TAPSE, right ventricular (RV) S wave velocity, GLS [-15.6% (IQR:4.39) to -13.7% (IQR:4.62)] and GCS [-17.8±3.58% to -16.1±2.94%] reduced significantly, while LVEF and GRS remained unchanged and lateral e' velocity increased. Conclusions: Despite favorable LV structural reverse remodeling and diastolic functional progress six months post-AVR, GLS and GCS assessed by CMR reduced compared to baseline, while LVEF remained unchanged. The clinical utility and timing of assessment of postoperative strain changes as a marker of systolic function evolution needs further research.